2006
DOI: 10.1001/archneur.63.11.nct60002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Intranasal Zolmitriptan in Acute Cluster Headache

Abstract: Background: Cluster headache is a form of primary headache in which attacks are rapid in onset with very severe pain. The mainstays of acute therapy are inhaled oxygen and sumatriptan succinate injection. Objective: To evaluate zolmitriptan nasal spray in the acute treatment of cluster headache. Methods: Ninety-two patients, aged 40 ± 10 years (mean ± SD) (80 men and 12 women), with International Headache Society-defined cluster headache were randomized into a placebo-controlled, double-blind crossover study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 129 publications
(56 citation statements)
references
References 26 publications
1
53
0
2
Order By: Relevance
“…Most required that participants had previously tolerated treatment with a triptan, and/or had no contraindications, but Ekbom 1991 and Ekbom 1993 recruited only sumatriptan-naïve participants. In four studies participants self-treated their headaches at home (Bahra 2000;Cittadini 2006;Van Vliet 2003), while in the other two medication was administered by a physician or nurse in hospital (Ekbom 1991;Ekbom 1993). We included these hospital-based studies because although the intervention was not self-administered in these cases, subcutaneous sumatriptan can be, and is commonly, self-administered.…”
Section: Assessment Of Reporting Biases-no Formal Tests Were Plannedmentioning
confidence: 99%
See 4 more Smart Citations
“…Most required that participants had previously tolerated treatment with a triptan, and/or had no contraindications, but Ekbom 1991 and Ekbom 1993 recruited only sumatriptan-naïve participants. In four studies participants self-treated their headaches at home (Bahra 2000;Cittadini 2006;Van Vliet 2003), while in the other two medication was administered by a physician or nurse in hospital (Ekbom 1991;Ekbom 1993). We included these hospital-based studies because although the intervention was not self-administered in these cases, subcutaneous sumatriptan can be, and is commonly, self-administered.…”
Section: Assessment Of Reporting Biases-no Formal Tests Were Plannedmentioning
confidence: 99%
“…The studies included participants with diagnoses of both episodic and chronic types of cluster headache, with between 56% and 75% having episodic-type headaches. Two studies reported some results for episodic and chronic headaches separately (Bahra 2000;Cittadini 2006). No participants were using prophylactic medication, and, as noted above, all studies had an appropriate washout period between study doses, co-analgesics or rescue medication.…”
Section: Assessment Of Reporting Biases-no Formal Tests Were Plannedmentioning
confidence: 99%
See 3 more Smart Citations